The Profile of BCR-ABL1 Fusion Gene in Childhood Leukemia at “Dharmais” Cancer Hospital - Mururul Aisyi; Puji Lestari; Siti Nadliroh; Anita Meisita; Didin Solachudin; Dewi Kristanti; Adhitya Bayu Perdana; Bambang Karsono (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: BCR-ABL1 fusion gene, which originated from t (9;22), is an important biomarker for diagnosis, therapeutic approach, and prognosis in childhood leukemia. However, there are no data in Indonesia about the profile of BCR-ABL1 fusion gene for this disease. This study intends to demonstrate the profile of the BCR-ABL1 fusion gene in childhood leukemia at “Dharmais” Cancer Hospital.Methods: This descriptive retrospective study included 79 patients with childhood leukemia who performed the BCR-ABL1 examination in “Dharmais” Cancer Hospital during 2008–2018. Demographic data, leukemia types, BCR-ABL1 examination results, and protein isoforms developed by BCR-ABL1 fusion were obtained from Cancer Registry Data.Results: Among 79 patients’ data recorded in this study, 65.8% (52/79) were male and 34.2% (27/79) were female. A total of 74.7% (59/79) patients were diagnosed with Chronic Myelogenous Leukemia (CML), 21.5% (17/79) with Acute Lymphoblastic Leukemia (ALL), and 3.8% (3/79) with Acute Myelogenous Leukemia (AML). The profile of positive BCR-ABL1 in CML patients was 72.8% (43/59). About 97.7% (42/43) of CML patients with positive BCR-ABL1 fusion gene expressed 210-kDa protein, while only 2.3% (1/43) expressed 190-kDa protein.Conclusions: This study found that, from a total of 79 respondents, 45 of them showed a positive BCR-ABL result, with details of 43 in CML and 2 in ALL. Among the total of 43 CML patients with positive BCR-ABL1, 42 (97.7%) of them expressed 210-kDa protein isoform. Further research to investigate the relationship between protein isoforms and their clinical effects may also be important to discuss. The valuable recommendation suggests that BCR-ABL1 examination should be performed for all childhood leukemia patients in Indonesia, especially for CML and ALL.